New Quinazolin-4(3H)-One Derivatives Incorporating Isoxazole Moiety as Antioxidant Agents: Synthesis, Structural Characterization, and Theoretical DFT Mechanistic Study - Yassine Rhazi; Riham Sghyar; Noemi Deak; Bouchra Es-Sounni; Bouchra Rossafi; Albert Soran; Mustapha Laghmari; Azize Arzine; Asmae Nakkabi; Khalil Hammani; Samir Chtita; Mohammed M. Alanazi; et al. (MDPI AG, 2024)
Background: This research centers on the development and spectroscopic characterization of new quinazolin-4(3H)-one-isoxazole derivatives (5a-e). The aim was to investigate the regioselectivity of the 1,3-dipolar cycloaddition involving arylnitriloxides and N-propargylquinazolin-4(3H)-one, and to assess the antioxidant properties of the synthesized compounds. The synthetic approach started with the alkylation of quinazolin-4(3H)-one using propargyl bromide, followed by a 1,3-dipolar cycloaddition reaction. Methods: The structural identification of the products was performed using various spectroscopic methods, such as IR, 1H, 13C, and HMBC NMR, HRMS, and single-crystal X-ray diffraction. To further examine the regioselectivity of the cycloaddition, Density Functional Theory (DFT) calculations at the B3LYP/6-31G(d) level were employed. Additionally, the antioxidant potential of the compounds was tested in vitro using DPPH (2,2-Diphenyl-1-picrylhydrazyl)radical scavenging assays. The reaction selectively produced 3,5-disubstituted isoxazoles, with the regiochemical outcome being independent of the substituents on the phenyl ring. Results: Theoretical calculations using DFT were in agreement with the experimental results, revealing activation energies of −81.15 kcal/mol for P-1 and −77.32 kcal/mol for P-2, favoring the formation of P-1. An analysis of the Intrinsic Reaction Coordinate (IRC) confirmed that the reaction proceeded via a concerted but asynchronous mechanism. The antioxidant tests demonstrated that the synthesized compounds exhibited significant radical scavenging activity, as shown in the DPPH assay. The 1,3-dipolar cycloaddition of arylnitriloxides with N-propargylquinazolin-4(3H)-one successfully resulted in novel 3,5-disubstituted isoxazoles. Conclusions: The experimental findings were well-supported by theoretical predictions, and the antioxidant assays revealed strong activity, indicating the potential for future biological applications of these compounds.